The Vasculopathy of Juvenile Dermatomyositis - Papadopoulou, Charalampia; McCann, Liza J. (Frontiers in Pediatrics, 2018)
Juvenile dermatomyositis (JDM) is a rare autoimmune disease mainly characterised by muscle and skin involvement. Vasculopathy is considered central to the pathogenesis of the disease. The exact nature of vasculopathy is not yet understood but it is a complex process with both an inflammatory and a non-inflammatory, occlusive component. Impaired function of JDM vasculature includes immune complex deposition, altered expression of cell adhesion molecules predominantly inducing Th17 cell infiltration, and endothelial cell dysfunction. Development of vasculopathy is associated with the severe extra-muscular manifestations of JDM, such as gastrointestinal and cardiac manifestations, interstitial lung disease, ulcerative skin disease or development of calcinosis, and portends a poor prognosis. Correlation of histopathological findings, autoantibodies and extensive diagnostic workup represent key elements to the early detection of vasculopathic features and early aggressive treatment. Monitoring of vasculopathy remains challenging due to the lack of non-invasive biomarkers. Current treatment approaches provide variable benefit, but better understanding of the essential pathogenic mechanisms should help lead to improved outcomes. Whilst acknowledging that evidence is limited, this review aims to describe the vasculopathy of JDM in the context of pathophysiology, clinical features and treatment of disease.